Environmental and Energy Efficiency Evaluation Based on Data Envelopment Analysis (DEA) - Sala-Garrido, Ramon; Molinos-Senante, María (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Efficiency and productivity assessment are essential to ensure the long-term financial sustainability of countries, services and processes. In the last few years, there has been an increasing interest in the environmental effects of economic activities, and the need to assess the environmental and energy efficiency has been internationally recognized. Energy and environmental efficiency assessments of decision-making units (DMUs), such as countries, utilities, processes and services are relevant and have strong implications for companies, regulators, stakeholders, policy makers, and customers. To improve both the decision-making process and the management of DMUs, fundamental and practical knowledge about energy and environmental efficiency and productivity is essential